2019
DOI: 10.1098/rsos.190255
|View full text |Cite
|
Sign up to set email alerts
|

Label-free sensitive detection of influenza virus using PZT discs with a synthetic sialylglycopolymer receptor layer

Abstract: We describe rapid, label-free detection of Influenza A viruses using the first radial mode of oscillations of lead zirconate titanate (PZT) piezoelectric discs with a 2 mm radius and 100 µm thickness fabricated from a piezoelectric membrane. The discs are modified with a synthetic sialylglycopolymer receptor layer, and the coated discs are inserted in a flowing virus suspension. Label-free detection of the virus is achieved by monitoring the disc radial mode resonance frequency shift. Piezo transducers with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
(74 reference statements)
0
16
0
Order By: Relevance
“…Results was analysed by monitoring resonance frequency shift of the disc radial mode with a detection limit of concentrations below 105 virus particles per millilitre. This study reported that Piezo transducers with sialylglycopolymer sensor layers have a long lifetime, a high sensitivity and the possibility of reproducible results [96].…”
Section: Piezoelectric Biosensormentioning
confidence: 92%
“…Results was analysed by monitoring resonance frequency shift of the disc radial mode with a detection limit of concentrations below 105 virus particles per millilitre. This study reported that Piezo transducers with sialylglycopolymer sensor layers have a long lifetime, a high sensitivity and the possibility of reproducible results [96].…”
Section: Piezoelectric Biosensormentioning
confidence: 92%
“…This was the first detection at aM range (140 aM for H5N1 and 14 fM for H1N1) using an impedimetric glycan biosensor. A similar approach was used by Erofeev and Gorelkin [141 , 142] , a syalylglycopolymer constituted of an H5N3 glycoprotein modified-polyacrylamide. The striking difference is the detection methodologies.…”
Section: Viral Respiratory Biosensorsmentioning
confidence: 99%
“…A detection limit as low as 1 ng mL −1 was obtained for influenza A H1N1 HA antigen at room temperature. Erofeev et al [84] described label-free rapid detection of influenza A virus using Ag-coated lead zirconate titanate (PZT) piezoelectric disks of Surface acoustic wave (SAW) sensor for influenza A virus detection. a) Preparation of bioactive surfaces for SAW sensors; b) photograph of a SAW sensor mounted onto a fixture with low-loss microwave probes; c) photomicroscopy image of the microwave probes in contact with the electrodes; and d) phase change versus time for a SAW sensor exposed to H1N1 HA antigen solutions of various concentrations and phosphate-buffered saline (PBS).…”
Section: Influenza a Virus: Group Vmentioning
confidence: 99%
“…Erofeev et al. [ 84 ] described label‐free rapid detection of influenza A virus using Ag‐coated lead zirconate titanate (PZT) piezoelectric disks of 100 µm thickness. The disks, modified with synthetic sialylglycopolymers based on a polymer matrix, which biospecifically bind the haemagglutinin proteins on the influenza viruses, were inserted in a flowing virus suspension.…”
Section: Piezoelectric Biosensorsmentioning
confidence: 99%